Factors Associated With Domestic Violence Against Women at Different Stages of Life: Findings From a 19-Year Longitudinal Dataset From the MINIMat Trial in Rural Bangladesh (2001–2020) - Ziaei, Shirin (Journal of interpersonal violence, 2023)
Despite the abundance of literature, longitudinal studies evaluating the factors associated with domestic violence (DV) at different stages and over longer periods of women’s lives are rare. We evaluated factors associated with physical and sexual DV during pregnancy, at 10-year, and 18-year follow-ups after pregnancy and within a 19-year period of life using a cohort of women (n = 1,126) who participated in the Maternal and Infant Nutrition Interventions, Matlab trial in rural Bangladesh. Data on women’s experience of DV, social and economic characteristics, empowerment, and family condition were recorded in a similar manner during pregnancy and at 10- and 18-year follow-ups, using standard questionnaires. Multivariate logistic regression models and generalized estimating equations were used to evaluate factors associated with women’s experience of physical and sexual violence at each discrete time point and over a period of 19 years, respectively. During pregnancy, women were more likely to experience violence if they were members of microcredit programs/non-governmental organizations (NGOs), living in an extended family and had lower wealth status. At the 10- and 18-year follow-ups, higher levels of decision-making and higher wealth status were protective against the experience of violence. At the 18-year follow-up, women with larger age differences from their husbands were less likely to experience violence, while membership in microcredit programs/NGOs was associated with higher odds of experiencing violence among women. Within a period of 19 years, a higher level of education, living in an extended family, higher decision-making level and higher wealth index were protective against the experience of violence, while membership in microcredit programs/NGOs was a risk factor. In conclusion, this study showed that correlates of violence might change at different time points in women’s life. Thus, policies and programs should consider the stage of women’s lives while planning interventions for addressing violence against women.